Imagens da crise: em busca de outras vozes - a crise econômica mundial e as crises permanentes do Brasil - Jacobini, Maria Lucia de Paiva (2013)
Our hypothesis is that the world today is going through several interrelated crises, especially those of the international financial crisis, the modern science paradigm and the permanent crisis that have always been a part of Latin American and, particularly, of Brazil. This research is divided in three parts: in the first, we work with Agamben s figures of the homo sacer, the sovereign, the state of exception as to create metaphors for the international financial turmoil and relate it to the crisis of Western modernity. In the second part, we show how the crisis was in Brazil and that, with its profane characteristics, created a solution to the economic problems different from the solutions proposed by international organizations. Finally, we emphasize the existence of a permanent crisis and of testimonies of its Muselmans, those not narrated by national media. The object of this thesis are the texts (written and pictorial) published by the newspaper Folha de S. Paulo, O Estado de S. Paulo and by magazines Carta Capital and Veja, between the years 2008 and 2012, on the financial and permanent crises. Via the relationship between these stories and theoretical discussion, our goal is to question how the selected newspapers and magazines address our (s) crisis (es) and how they emphasize economic aspects despite the others that distinguish the permanent state of exception. In order to do that, we use photography thinkers such as Kossoy, Barthes, Flusser, Sontag and Belting to approach the use of the image by the media and its power in memory formation about crises, accompanied by Sousa Santos, Laplantine & Nouss, Martín-Barbero, Viveiros de Castro and Mignolo that study the connection between communication and Latin American culture and its internal (profane) mechanisms that face the uniformity widespread by modern science. Lotman s thoughts on memory, in a dialogue with Agamben s notion of testimony, will help to decipher stories told in the news and the need for disclosure of unpublished voices - those of the permanent local crises. Therefore, we believe that there is a complexity in the Latin American context that can accept both Agamben s negativity and the profane possibilities envisioned by Viveiros de Castro. Besides, a reflection on how the media deal with the crises that exist in Brazil and around the world is significant for our understanding of the intentions intrinsic to the choice of news, their images and to their ability to make space for other narratives about the different local stories